2010
DOI: 10.1086/650471
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance of Skeletal Muscle Atrophy in Spontaneous and Facultative Hibernators

Abstract: Smooth and skeletal muscle changes were compared from overwintering white-tailed prairie dogs, spontaneous hibernators that undergo regular, low-temperature torpor bouts, and black-tailed prairie dogs, facultative hibernators that use sporadic, moderate-temperature torpor bouts. The objectives were to assess the abilities of these two species with dramatically different torpor patterns (1) to conserve skeletal muscle morphology, protein, and strength and (2) to use labile protein in the small intestine and liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 75 publications
1
49
0
Order By: Relevance
“…Therefore, there appears to have been significant skeletal muscle atrophy and reduction of body fat in response to torpor conditions. Some previous studies on hibernation have also found significant skeletal muscle atrophy; for example, 13 to 30% skeletal muscle mass loss in a number of species of hibernating mammals (Musacchia et al, 1989;Rourke et al, 2004;Cotton and Harlow, 2010). However, in other previous work, there was no evidence of skeletal muscle atrophy during hibernation (Rourke et al, 2004;Lohuis et al, 2007a;Lee et al, 2008;Cotton and Harlow, 2010).…”
Section: Morphologymentioning
confidence: 73%
See 2 more Smart Citations
“…Therefore, there appears to have been significant skeletal muscle atrophy and reduction of body fat in response to torpor conditions. Some previous studies on hibernation have also found significant skeletal muscle atrophy; for example, 13 to 30% skeletal muscle mass loss in a number of species of hibernating mammals (Musacchia et al, 1989;Rourke et al, 2004;Cotton and Harlow, 2010). However, in other previous work, there was no evidence of skeletal muscle atrophy during hibernation (Rourke et al, 2004;Lohuis et al, 2007a;Lee et al, 2008;Cotton and Harlow, 2010).…”
Section: Morphologymentioning
confidence: 73%
“…Some previous studies on hibernation have also found significant skeletal muscle atrophy; for example, 13 to 30% skeletal muscle mass loss in a number of species of hibernating mammals (Musacchia et al, 1989;Rourke et al, 2004;Cotton and Harlow, 2010). However, in other previous work, there was no evidence of skeletal muscle atrophy during hibernation (Rourke et al, 2004;Lohuis et al, 2007a;Lee et al, 2008;Cotton and Harlow, 2010). Muscle atrophy can be caused by reductions in the load or activity experienced by the muscle (Musacchia et al, 1988;Narici and Maganaris, 2007;Phillips et al, 2009).…”
Section: Morphologymentioning
confidence: 84%
See 1 more Smart Citation
“…Whereas hibernating U. americanus lower their body temperature by only 2-5°C (Lohuis et al, 2007b), ground squirrels in deep torpor reduce core temperature to near ambient (approximately 4°C), yet both species show minimal muscle atrophy despite months of inactivity. Furthermore, a study examining two species of prairie dogs found no difference in the extent of muscle or strength loss between the two despite differences in their hibernation strategies (one experiencing normal torpor cycles with very low core temperatures, the other being facultative hibernators that use sporadic, moderate-temperature torpor cycles) (Cotton and Harlow, 2010).…”
Section: Hibernating Mammals As Models Of Muscle Disuse Atrophymentioning
confidence: 99%
“…However, recent investigations have examined the structure, function and plasticity of muscles in organisms that experience natural periods of muscle disuse or immobilisation, such as aestivating frogs and hibernating mammals (Cotton and Harlow, 2010;Harlow et al, 2001;Hudson and Franklin, 2002a;Mantle et al, 2009;Nowell et al, 2011;Symonds et al, 2007;Young et al, 2011). These studies have shown that animals which undertake extended bouts of natural immobility (i.e.…”
Section: Introductionmentioning
confidence: 99%